2010
DOI: 10.1590/s0037-86822010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre incidência de dengue, pluviosidade e densidade larvária de Aedes aegypti, no Estado de Goiás

Abstract: RESUMOIntrodução: A densidade larvária de Aedes aegypti flutua de acordo com as variações climáticas sazonais, elevando-se nas estações de maior pluviosidade, em função do número de potenciais criadouros disponíveis, o que predispõe ao aumento da incidência de dengue. Este estudo teve o objetivo de mostrar a associação entre os casos de dengue, a pluviosidade e o índice de infestação predial. Métodos: Os municípios foram estratificados de acordo com transmissão e risco de dengue, e infestados ou não pelo mosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 16 publications
0
21
0
19
Order By: Relevance
“…En el estado de Goiás, Souza, et al, (31) determinaron que se registraron incrementos en la transmisión de la enfermedad durante los períodos de alta precipitación y que fue menor el número de casos en las estaciones de poca lluvia.…”
Section: Discussionunclassified
“…En el estado de Goiás, Souza, et al, (31) determinaron que se registraron incrementos en la transmisión de la enfermedad durante los períodos de alta precipitación y que fue menor el número de casos en las estaciones de poca lluvia.…”
Section: Discussionunclassified
“…The climate of the state of Goiás is Central Brazil Tropical, with two well-defined seasons: extremely dry in the middle of the year and rainy in the summer, with a period of drought that lasts from 5 to 6 months (May to September) and a rainy season that lasts from October to April 31 . The climate of Goiás is similar to the climate of the other states located in the Central-West region and the cycles of rainfall seasonality are similar to those of the rest of Brazil, except for some regions of the Northeast, which have the Eastern Northeast Tropical climate, and of the Northern Amazon, which have Representative values for temperature and relative air humidity were shown; it is believed that only the maximum temperatures exercise a strong influence on the larvae population.…”
Section: Rainfallmentioning
confidence: 99%
“…Many studies that employed entomological surveys 22,23,26,29,[37][38][39] have shown higher values of infestation of eggs, larvae and vectors in the rainy period; however, the positive breeding sites persist in the drought period, a fact that is favored by the mosquito's facility to adapt to the human environment, through natural and/or artificial reservoirs 31,34,40,41 . The rainfall data referring to the months of highest number of notification of cases showed a slight relationship among one another.…”
Section: Rainfallmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados nos municípios de São Luis do Maranhão 16 e Teresina-PI, 12 e nos estados de Pernambuco 14 e Goiás. 17 Determinados tipos de recipientes podem assumir papéis diferenciados na produção de adultos em diferentes regiões, daí atribuir-se grande importância aos reservatórios domiciliares como criadouro de Aedes aegypti, justificando a persistência na ocorrência da doença durante todos os meses do ano, ainda que em áreas de clima semi-árido. Esses reservatórios permanentes de água para consumo humano propiciam excelentes condições para a reprodução do vetor, contribuindo para a manutenção de populações desse mosquito, mesmo em períodos não favoráveis como os meses de baixas precipitações.…”
Section: Discussionunclassified